PENGEMBANGAN TRAINER PENGAPLIKASIAN PROGRAMMABLE LOGIC CONTROLLER (PLC) SEBAGAI SISTEM KONTROL TRAFFIC LIGHT 4 JALUR PORTABLE UNTUK SISWA SMK - I Putu Oka Kusuma Yasa; I Putu Suka Arsa; I Nyoman Santiyadnya (Jurnal Pendidikan Teknik Elektro Undiksha, 2021)
This study aims to design and create a Media Trainer for the Application of a Programmable Logic Controller (PLC) as a Portable 4 Line Traffic Light Control System, to know the media as a supporter of the learning process, and to find out the response of students to learning media in the Electrical Power Installation Engineering Expertise Program (TITL). This research includes the R&D (Research and Development) research model. The study used a questionnaire or questionnaire as an instrument of data collection by content experts, media experts, and students. From the results of the study obtained: the results of the expert trial obtained a value of 98.07% with a very feasible classification, the results of the media expert trial obtained a percentage of 96.15% with a very feasible classification, the results of the small group test the lowest result was in respondent 5 (R5) with a score of 49 which is considered very good, the results of the large group test have the lowest respondent score, namely respondent 4 (A4) with a score of 49 which is classified as very good. Based on the results of the research, the Media Trainer Application of Programmable Logic Controller (PLC) as a Portable 4 Line Traffic Light Control System that is suitable for use in the learning process of Electric Motor Installation in the Electrical Power Installation Engineering Expertise Program (TITL) SMK Negeri 3 Singaraja.